Pendidikan pancasila di perguruan tinggi sebagai benteng karakter bangsa dalam arus globalisasi - Agus, Andi Aco (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2025)
Pancasila is very important as a bastion of national character, as the foundation of the state and a way of life. Pancasila serves to preserve the nation's identity so that it is not uprooted from its cultural roots. Pancasila education in higher education institutions is a key instrument in instilling values in the younger generation who will one day lead a nation that is integrated, globally competitive, and rooted in Pancasila, capable of filtering foreign cultures and becoming citizens who love their homeland. The pitfalls of globalization for the nation's character are foreign cultures, individualism, materialism, digital technology, misuse of social media, moral degradation, the free market economy, value orientation, weakening of the spirit of mutual cooperation, tolerance, and nationalism. Strategies to strengthen Pancasila values in the younger generation include innovative learning curricula, project-based learning, real-case discussions, comprehensive studies, lecturer role models, strengthening extracurricular activities, increasing forums that foster a spirit of nationalism, utilizing technology, and creating creative digital content based on Pancasila values